2019
DOI: 10.1002/ps.5609
|View full text |Cite
|
Sign up to set email alerts
|

Immunity of an insect herbivore to an entomovirus is affected by different host plants

Abstract: BACKGROUND Interactions between herbivorous insects and entomoviruses may depend on host plant, perhaps mediated through changes in herbivore innate immunity. RESULTS Caterpillars (Spodoptera exigua) fed Glycine max had high viral loads and low melanization rates together with low melanization enzyme [PO, DDC, TH] activities and gene expressions. Caterpillars fed Ipomoea aquatica had low viral loads and high melanization, gene activities and gene expressions while those fed Brassica oleracea or artificial diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 54 publications
3
12
0
Order By: Relevance
“…Tri‐trophic interactions among plants, insect herbivores and entomoviruses are of increasing interest in entomology and ecology (Cory & Myers, 2004; Shikano, 2017; Wang et al., 2020). Among such tri‐trophic interactions, host plant‐mediated effects on the susceptibility of insect herbivores to entomoviruses have received particular attention (Cory & Hoover, 2006; Shikano et al., 2010; Wan et al., 2016, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tri‐trophic interactions among plants, insect herbivores and entomoviruses are of increasing interest in entomology and ecology (Cory & Myers, 2004; Shikano, 2017; Wang et al., 2020). Among such tri‐trophic interactions, host plant‐mediated effects on the susceptibility of insect herbivores to entomoviruses have received particular attention (Cory & Hoover, 2006; Shikano et al., 2010; Wan et al., 2016, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…(2018) and Wang et al. (2020) have reported that the differences in virus susceptibility depend on the variation in melanization enzymes of humoral immunity (i.e. phenoloxidase, dopa decarboxylase and tyrosine hydroxylase) of herbivores.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, more hemocytes denote stronger resistance against entomovirus infection and also greater immunity. In a previous study, 43 we found that S. exigua feeding on I. aquatica had the lowest mortality and the lowest viral load, followed by Brassica oleracea . This was consistent with Shikano et al 8 .…”
Section: Discussionmentioning
confidence: 62%
“…The purified NPV were diluted 100‐fold with PBS, and the NPV concentration (1.26 × 10 7 OB mL −1 ) (occlusion body, OB) was obtained by Thomas hemocytometer under a phase‐contrast microscope at 400× magnification. The virus was diluted with sterile water to a concentration of 1.26 × 10 4 OB mL −1 for this experiment to avoid excessive larval mortality 7,43 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation